Fuzzy Based Gain Scheduled PI Controller for an Isolated Wind Diesel Hybrid Power System - Goutham Govind Raju; S. Mohamed Ali (Bulletin of Electrical Engineering and Informatics, 2012)
Electrical power is the vital input for the economic development of any developing country. At their zenith, many excellent methods for the generation of power have been developed. The cost of supplying electrical power through grid to rural areas is becoming excessively high due to large investments in transmission and distribution lines, centralized power generating stations and line losses. For these reasons, the stand alone decentralized power generating stations with non– conventional energy sources like wind, biomass, solar energy, micro and mini hydel sources are being considered for electrifying remote rural areas. Hence in this paper an isolated wind–diesel hybrid power system with superconducting magnetic energy storage unit is considered. The hybrid power system is normally equipped with a control system, which functions to reduce the system frequency oscillations and makes the wind turbine generator power output follow the performance curve when the system is subjected to wind/load disturbances. Usually PI controllers are employed in these systems. Unfortunately, since the operating point continuously changes depending on the demand of consumers, this constant gain PI controller are unsuitable to other operating points. Therefore, this paper describes the application of the fuzzy gain scheduling on the PI controller for an isolated wind – diesel hybrid power system with superconducting magnetic energy storage unit.